SCOTUS 2023
XVII, 224 p. 2 illus., 1 illus. in color.
Keywords: Each year, the Supreme Court of the United States announces new rulings with deep consequences for our lives. This sixth volume in Palgrave’s SCOTUS series describes, explains, and contextualizes the landmark cases of the US Supreme Court in the term ending 2023. With a close look at cases involving key issues and debates in American politics and society, SCOTUS 2023 tackles the Court’s rulings on affirmative action, LGBT equality, internet platform liability, the Clean Water Act, immigration enforcement, and more. Written by notable scholars in political science and law, the chapters in SCOTUS 2023 present the details of each ruling, its meaning for constitutional debate, and its impact on public policy or partisan politics. Finally, SCOTUS 2023 offers an analysis of Justice Ketanji Brown Jackson's first year on the court, as well as court reform. Morgan Marietta is Dean of the Center for Economics, Politics & History. Prior to joining the University of Austin. He is the author of The Politics of Sacred Rhetoric: Absolutist Appeals and Political Influence (2012); A Citizen’s Guide to American Ideology (2011); A Citizen’s Guide to the Constitution and the Supreme Court (2013); and coauthor of One Nation, Two Realities: Dueling Facts in American Democracy (2019). Howard Schweber is Professor of Political Science and an affiliate faculty member of the Law School at the University of Wisconsin-Madison. He is the author of five books, including The Legacy of Antonin Scalia (2018), Democracy and Authenticity: Toward a Theory of Public Justification (2011), and The Language of Liberal Constitutionalism, (2007). He is the editor of Constitutional Studies.